"Throughness": A Story About Songwriting as Auto/Ethnography. (March 2018) - Carless, David
A recent special issue of Qualitative Inquiry (December 2016) throws a welcome spotlight on the place of songs within qualitative research. In this essay, I share a story that contributes to the gathering conversation around music and songs as a (perhaps unique) form of qualitative inquiry. My contribution focuses specifically on song writing as a form of research, which has received limited attention to date within the qualitative inquiry literature. The story is inspired by recent explorations of songwriting as reflexive practice, and I share it with the aim of expanding understanding and inviting further dialogue on the processes of writing (songs as) qualitative research.